2018
DOI: 10.1016/j.ultrasmedbio.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Liver Ultrasound Elastography: An Update to the World Federation for Ultrasound in Medicine and Biology Guidelines and Recommendations

Abstract: The World Federation for Ultrasound in Medicine and Biology has produced these guidelines for the use of elastography techniques in liver diseases. For each available technique, the reproducibility, results and limitations are analyzed, and recommendations are given. This set of guidelines updates the first version, published in 2015. Since the prior guidelines, there have been several advances in technology. The recommendations are based on the international published literature, and the strength of each reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
436
1
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 443 publications
(466 citation statements)
references
References 212 publications
(251 reference statements)
11
436
1
18
Order By: Relevance
“…In this study, we found that the intraobserver and interobserver agreement coefficients were higher for both the 10‐ and 20‐mm diameters than for the 30‐mm diameter. In addition, the results of this study also indicated that a Q‐Box with a diameter of 30 mm had the largest CV of all diameters, which may have been due to SWE signal dropout and inhomogeneous regions that often occur at the borders of the field of view . Two‐dimensional SWE provides a real‐time quantitative LS map (elasticity map) that can be used to evaluate the spatial heterogeneity of LS .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this study, we found that the intraobserver and interobserver agreement coefficients were higher for both the 10‐ and 20‐mm diameters than for the 30‐mm diameter. In addition, the results of this study also indicated that a Q‐Box with a diameter of 30 mm had the largest CV of all diameters, which may have been due to SWE signal dropout and inhomogeneous regions that often occur at the borders of the field of view . Two‐dimensional SWE provides a real‐time quantitative LS map (elasticity map) that can be used to evaluate the spatial heterogeneity of LS .…”
Section: Discussionmentioning
confidence: 85%
“…Two‐dimensional SWE provides a real‐time quantitative LS map (elasticity map) that can be used to evaluate the spatial heterogeneity of LS . As a result, the placement of the Q‐Box was adjusted to avoid errors . However, a diameter of 30 mm for the Q‐Box represents the largest circle in the field of view; therefore, avoiding errors by adjusting the placement of the Q‐Box is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…The interquartile range measures the statistical dispersion between the upper and lower quartiles. A data set of the liver is considered good with an IQR/median of less than 0.3 (elastography measured in kilopascals) or less than 0.15 (elastography measured in meters per second) . Thresholds for ARFI values of the bowel wall are currently lacking and are an area of study.…”
Section: Unique Adjunctive Us Biomarkersmentioning
confidence: 99%
“…This has favoured the development of alternative non‐invasive strategies, which have been an area of intensive research over the past decade. Although none of the non‐invasive tests adequately discriminate NASH from simple steatosis in patients with NAFLD, they are now extensively used in liver clinics to detect advanced liver fibrosis and are recommended by international guidelines …”
Section: Introductionmentioning
confidence: 99%